Challenges of event detection from social media streams - Zubair Al-Dyani, Wafa; Hussein Yahya, Adnan; Kabir Ahmad, Farzana (International Journal of Engineering and Technology, 2018)
The area of Event Detection (ED) has attracted researchers’ attention over the last few years because of the wide use of social media.Â Many studies have examined the problem of ED in various social media platforms, like Twitter, Facebook, YouTube, etc. The ED task for social networks involves many issues, including the processing of huge volumes of data with a high level of noise, data collection and privacy issues, etc.Â Hence, this article discusses and presents the wide range of challenges encountered in the ED process from unstructured text data for the most popular Social Networks (SNs), such as Facebook and Twitter. The main goal is to aid the researchers to understand the main challenges and to discuss the future directions in the ED area. Â